Relative Contributions of Pulse Pressure and Arterial Stiffness to Cardiovascular Disease The Framingham Heart Study - Niiranen TJ; Kalesan B; Mitchell GF; Vasan RS (LIPPINCOTT WILLIAMS & WILKINS, 2022)
Pulse pressure has been frequently used as a surrogate marker of arterial compliance. However, the prevalence and prognostic significance of mismatch between pulse pressure and arterial stiffness remains unclear. We measured carotid-femoral pulse wave velocity (CFPWV) and central pulse pressure (CPP) in 2119 Framingham Offspring Cohort participants (mean age, 60 years; 57% women). The participants were divided into 4 groups according to CPP and CFPWV status (categorized as high/low based on >= age- and sex-specific median values) and followed up for cardiovascular disease (CVD) events. At baseline, 832 of 2119 (39%) participants had discordant CPP and CFPWV status, 417 with low CPP and high CFPWV, and 415 with high CPP and low CFPWV. The multivariable-adjusted risk for CVD events (n= 246; median follow-up, 12.6 years) in individuals with a CPP-CFPWV mismatch (hazard ratio for low CPP with high CFPWV, 1.21; 95% CI, 0.83-1.76; hazard ratio for high CPP with low CFPWV, 0.76; 95% CI, 0.49-1.19) was comparable with the CVD risk observed in the low CPP with low CFPWV (referent group). In contrast, participants with a high CPP with high CFPWV (hazard ratio, 1.52; 95% CI, 1.10-2.11) experienced significantly increased CVD risk. The interaction term between CPP and CFPWV status on CVD risk was borderline significant in the multivariable model (P=0.08). Our results demonstrate that pulse pressure-arterial stiffness mismatch is common in the community. CFPWV may modify the association of CPP with CVD risk, with the greatest risk being observed in those with elevated CPP and CFPWV.